When do investors go green? Evidence from a time-varying asset-pricing model - Lucia Alessi; Elisa Ossola; Roberto Calogero Panzica (European Commission, 2021)
This paper studies the evolution of the greenium, i.e. a risk premium linked to firms' greenness and environmental transparency, based on individual stock returns. We estimate an asset pricing model with time-varying risk premia, where the greenium is associated to a priced 'greenness and transparency' factor, which considers both companies' greenhouse gas emissions and the quality of their environmental disclosures. We show that investors in the European equity market tend to accept lower returns, ceteris paribus, to hold greener and more transparent assets when the shift of the economy towards low-carbon becomes more credible. This happened after the Paris Agreement, the first Global Climate Strike and the announcement of the EU Green Deal. Signals going in the opposite direction, such as the US withdrawal from the Paris Agreement, increasing fossil fuel prices and more bad news about climate change, are associated with increases in the greenium.
Keywords: G01; G11; G12; Q01; 330; Climate risk; environmental disclosure; conditional factor models; asset pricing